Teaching Listening Through Podcast - Retno Rahayuningsih; Yanti Rosalinah; Ibnu Subroto (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Listening is one of the skills in teaching English. Listening is not passive ability but active communication. Listening aims to understand and respond to what we hear. When we hear, we always give response either through direct spoken language or body language. To get maximum results, teachers must be able to use media that can facilitate and motivate students in the learning process of hearing. In this case, the media that is currently being used is podcast audio. Podcasts come from the words "iPod" and "broadcast" which produce audio and video files episodically that can be downloaded and listened to by personal computers, tablets, smart phones, or other audio/video device and listeners can listen and learn all the interesting material they need. The purpose of this study is to introduce the use of audio podcasts as a media portable for listening learning, in addition to this research aims to apply audio podcast media in the process of teaching English the 8th students at SMP 181 Jakarta. The teaching process through; interviews, observations, literary studies, and the internet. Additionally, to collect results from significant differences before and after using audio podcasts, the authors used pre-tests and post-tests during observation. The study's findings include: 1) the advantage of teaching Listen through audio podcasts is that authors find that podcasts can help students feel comfortable while they listen to questions. Students can repeat listening to missed or unheard sentences. 2) Through audio podcasts make it easy for teachers to teach students online without offline process, 3) through audio podcasts are very effective in improving students' ability in listening skills for the 8th students at SMP 181 Jakarta. Through the Audio Podcast, the author makes students enjoy and happy to listen. Because, audio podcasts make students easy to be applied